5-HT2C receptor activation decreases appetite and body weight in obese subjects. - Sargent, P; Sharpley, A; Williams, C; Goodall, E; Cowen, P (1997)
We studied the effect of 2 weeks administration of the 5-HT2C receptor agonist, m-chlorophenylpiperazine (mCPP), on appetite and body weight in 18 moderately obese subjects in a double-blind, placebo-controlled trial, mCPP caused a small but significant (0.75 kg) reduction in body weight and in subjective ratings of hunger. Plasma prolactin was significantly elevated by the final dose of mCPP. Our data suggest that during 2 weeks treatment in humans, mCPP may continue to activate brain 5-HT2C receptors, and that this effect is associated with decreases in appetite and body weight.